Bank lending and firm internal capital markets following a deglobalization shock - Björn Imbierowicz; Arne J. Nagengast; Esteban Prieto; Ursula Vogel (Deutsche Bundesbank, 2025)
The pace of globalization has slowed since the global financial crisis, raising concerns about widespread deglobalization and market fragmentation. We examine the effects of a deglobalization shock on bank lending, firm internal capital markets, and the real economy. Leveraging a unique dataset that combines a credit register with foreign direct investment (FDI) data, we are able to observe both domestic and cross-border credit exposures of German banks as well as internal capital market dynamics within multinational corporations (MNCs) - a feature rarely available in other countries' data. We analyze the response to the Brexit referendum shock. On average, German banks reduced lending to United Kingdom (UK) firms following the shock due to increased uncertainty about future losses. More prudent banks reduced their credit more extensively, and less profitable subsidiaries experienced greater reductions. However, UK subsidiaries of large MNCs, with access to internal capital markets, offset this credit supply shock through internal funding, shielding them from negative real effects. We find that non-UK subsidiaries play a crucial role in internal capital markets by securing external financing and reallocating funds to support UK affiliates. Well capitalized banks reallocated lending to firms outside the UK, particularly those of German MNCs. Our findings underscore that while international financial frictions following deglobalization shocks can imply negative real effects, firms integrated into global networks mitigate these impacts through internal capital markets.
Keywords: F23; F34; F36; G21; 330; Bank lending; deglobalization shock; policy uncertainty; real-financial linkages; internal capital markets